2016
DOI: 10.1155/2016/6195494
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Current Diagnostic Criterion of HbA1c with Fasting and 2-Hour Plasma Glucose Concentration

Abstract: To determine the effectiveness of hemoglobin A1c (HbA1c) ≥ 6.5% in diagnosing diabetes compared to fasting plasma glucose (FPG) ≥ 126 mg/dL and 2-hour plasma glucose (2hPG) ≥ 200 mg/dL in a previously undiagnosed diabetic cohort, we included 5,764 adult subjects without established diabetes for whom HbA1c, FPG, 2hPG, and BMI measurements were collected. Compared to the FPG criterion, the sensitivity of HbA1c ≥ 6.5% was only 43.3% (106 subjects). Compared to the 2hPG criterion, the sensitivity of HbA1c ≥ 6.5% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 41 publications
3
37
0
2
Order By: Relevance
“…Elevated HbA1c levels in diabetic patients were first reported in 1969 [ 31 ] and were shown to indicate aggravated glucose levels over a 3-month period [ 32 ]. Since the HbA1c level was included as a diagnostic criterion by the American Diabetes Association in 2010, many researchers have explored its diagnostic efficacy and have examined the optimal cutoff values [ 10 33 34 35 36 ]. These studies suggested that the HbA1c level was of low sensitivity when used to screen for diabetes, and the authors concluded that the cutoff values had to be reduced to increase sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated HbA1c levels in diabetic patients were first reported in 1969 [ 31 ] and were shown to indicate aggravated glucose levels over a 3-month period [ 32 ]. Since the HbA1c level was included as a diagnostic criterion by the American Diabetes Association in 2010, many researchers have explored its diagnostic efficacy and have examined the optimal cutoff values [ 10 33 34 35 36 ]. These studies suggested that the HbA1c level was of low sensitivity when used to screen for diabetes, and the authors concluded that the cutoff values had to be reduced to increase sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…In a Canadian context, A1C may identify more people as having diabetes than FPG (27). However, other studies suggest A1C may not identify as many people as having diabetes compared to FPG or 2hPG (28).…”
Section: Diabetesmentioning
confidence: 91%
“…In addition, significant differences in HbA1c cut-off points for DM2 according to ethnicity, age, sex, and population prevalence of diabetes were noted [ 7 , 8 ]. In US adults Karnchanasorn et al [ 9 ] reported also found that HbA1c ≥ 6.5% had a low diagnostic capacity relative to both FPG and OGTT, suggesting that a substantial number of cases of DM2 would be missed using this criterion. This data, from over 5000 participants of the NHANES 2005–2010 showed that of 392 subjects who met ADA criterion for DM2 according to OGTT only 28.1% were identified by HbA1c, while of 245 subjects who met FPG cut points only 43.3% were also diagnosed by HbA1c.…”
Section: Discussionmentioning
confidence: 99%
“…Although the risk factors [ 7 ] and the criteria for the diagnosis of DM2 are well defined [ 5 , 6 ], there is ongoing debate as to whether these criteria are universally associated with the future risk of vascular complications [ 8 ]. Furthermore, a recent study found that based on the current cut-points, HbA1c, had a poor capacity to detect DM2 in US adults relative to OGTT and FPG [ 9 ]. Given the expense of conducting all three tests and the fact that in Colombia HbA1c is the most expensive of these, we aimed to determine the capacity of FPG, OGTT and HbA1c to detect DM2 in Colombian adults, and if their simultaneous assessment increases the diagnosis of DM2 according to the criteria of the Colombian guidelines for diabetes and the American Diabetes Association (ADA) [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%